Effects of a 20-min nap post normal and jet lag conditions on P300 components in athletes - Petit, E.; Bourdin, H.; Tio, G.; Yenil, O.; Haffen, E.; Mougin, F. (International Journal of Sports Medicine, 2018)
Post-lunch sleepiness belongs to biological rhythms. Athletes take a nap to counteract afternoon circadian nadir, in prevision of disturbed sleep. This study examined the effects of brief post-lunch nap on vigilance in young and healthy athletes. The P300 components, physiological and cognitive performances were assessed either after nap or rest, following a night of normal sleep (NSC) or simulated jet lag condition (5-h advance-JLC). P300 wave is the positive deflection at about 300 ms in response to a rare stimulus, representing higher information processing. P300 amplitude reflects the amount of attention allocated whereas P300 latency reflects time spent on stimulus classification. P300 amplitude was significantly increased (Fz:11.14±3.0vs9.05±3.2 µV; p<0.05) and P300 latency was shorter (Pz:327.16±18.0vs344.90±17.0 ms; p<0.01) after nap in NSC. These changes were accompanied by lower subjective sleepiness (19.7±9.6vs27.5±16.5; p<0.05) and decrease in mean reaction times (MRT: divided attention, 645.1±74.2vs698±80.4 ms; p<0.05). In contrast, in JLC, only P300 amplitudes (Fz:10.30±3.1vs7.54±3.3 µV; p<0.01 and Cz: 11.48±3.1vs9.77±3.6 µV; p<0.05) increased but P300 latencies or MRT did not improve. These results indicated improvements in speed of stimulus evaluation time. Napping positively impacts on cognitive processing, especially when subjects are on normal sleep schedules. A nap should be planned for athletes whose performance requires speedy and accurate decisions.